Glucocorticoids as cytokine inhibitors: role in neuroendocrine control and therapy of inflammatory diseases - Giamila Fantuzzi; Pietro Ghezzi (Mediators of Inflammation)
Glucocorticoids are potent inhibitors of inflammation and endotoxic shock. This probably occurs through an inhibition of the synthesis of pro-inflammatory cytokines as well as of many of their toxic activities. Therefore, endogenous glucocorticoids (GC) might represent a major mechanism in the control of cytokine mediated pathologies. GC inhibit the synthesis of cytokines in various experimental models. Adrenalectomy or GC antagonists potentiate TNF, IL-1 and IL-6 production in LPS treated mice. GC inhibit the formation of arachidonic acid metabolites and the induction of NO synthase. They also inhibit various activities of cytokines including toxicity, haemodynamic shock and fever. Adrenalectomy sensitizes to the toxic effects of LPS, TNF and IL-1. On the other hand, GC potentiate the synthesis of several cytokine induced APP by the liver. Since many of these proteins have anti-toxic activities (antioxidant, antiprotease etc.) or bind cytokines, this might well represent a GC mediated protective feedback mechanism involving the liver. Not only do GC inhibit cytokines, but in vivo LPS and various cytokines (TNF, IL-1, IL-6) increase blood GC levels through a central mechanism involving the activation of the HPA. Thus, this neuroendocrine response to cytokines constitutes an important immunoregulatory feedback involving the brain.